2013
DOI: 10.1371/journal.pone.0055162
|View full text |Cite
|
Sign up to set email alerts
|

Differential Psychological Impact of Internet Exposure on Internet Addicts

Abstract: The study explored the immediate impact of internet exposure on the mood and psychological states of internet addicts and low internet-users. Participants were given a battery of psychological tests to explore levels of internet addiction, mood, anxiety, depression, schizotypy, and autism traits. They were then given exposure to the internet for 15 min, and re-tested for mood and current anxiety. Internet addiction was associated with long-standing depression, impulsive nonconformity, and autism traits. High i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
80
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 29 publications
15
80
2
2
Order By: Relevance
“…Finkenauer and colleagues (2012) also reported the first empirical study for examining autistic traits in adults and claimed that strong autistic traits could predict compulsive Internet use, but not frequent Internet use. Their findings were further supported by a recent study demonstrating a positive relationship between Internet addiction and the autistic trait (Romano, Osborne, Truzoli, & Reed, 2013). Those findings indicated that possessing certain kinds of traits may result in increasing the vulnerability for Internet addiction.…”
supporting
confidence: 55%
“…Finkenauer and colleagues (2012) also reported the first empirical study for examining autistic traits in adults and claimed that strong autistic traits could predict compulsive Internet use, but not frequent Internet use. Their findings were further supported by a recent study demonstrating a positive relationship between Internet addiction and the autistic trait (Romano, Osborne, Truzoli, & Reed, 2013). Those findings indicated that possessing certain kinds of traits may result in increasing the vulnerability for Internet addiction.…”
supporting
confidence: 55%
“…A person's interaction with society and one's self has been intensified with the increase of technology in the last two decades (Romano, Osborne, Truzoli, & Reed, 2013). This change and progression in technology though good, has had an impact on people that was unexpected.…”
Section: Transparency In Information Usementioning
confidence: 99%
“…Por ejemplo, varios estudios han demostrado que la adicción a una actividad comportamental (e.g. juegos de azar) puede conducir a dificultades en la comunicación y el desempeño social (Echeburúa & De Corral, 2010;Romano, Osborne, Truzoli & Reed, 2013;Wu, Cheung, Ku & Hung, 2013). Sin embargo, la literatura con respecto a este último problema es aún limitada.…”
Section: Aspectos Históricos Del Concepto De Dependenciaunclassified